Correlation Between Birth History and Development of Children Aged 0-5 Years - Binuko Amarseto; Almas Awanis (GLOBAL HEALTH SCIENCE GROUP, 2022)
The process of growth and development is closely related to health factors, in other words, only healthy children can be expected to have an optimal growth and development process. Although the process of child growth and development takes place naturally, the process is very dependent on adults or parents. The reason this study aims to see the relationship that occurs with children aged 0-5 years on their growth and development of various variables in the history of childbirth, including normal/premature birth, baby's weight, and the type of delivery whether normal or caesarean section. This study used a cross sectional approach. The results of this study found that the history of births with growth and development of children aged 0-5 years in the working area of the Grogol Sukoharjo Community Health Center. The data and results of this study can be used as a reference that the type of birth and delivery that is not normal has no effect on the growth and development of children aged 0-5 years.